2023
DOI: 10.1371/journal.pone.0284422
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experience of undergoing maintenance hemodialysis. An interview study from Ethiopia

Abstract: Background People with kidney failure require renal replacement therapy in the form of dialysis or a kidney transplant for survival. Many facets of their life, both within and outside the dialysis unit, are impacted by the management of this disease. It is important to comprehend the experiences of people undergoing hemodialysis in order to improve the care provided to them. Therefore, this study aimed to explore the experiences of patients undergoing maintenance hemodialysis in Ethiopia. Methods A qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…A single hemodialysis session in Ethiopia has an out-of-pocket cost of $100, which is 11% of the per capita Ethiopian GDP and is, therefore, inaccessible to almost everyone. 17 analysis, per capita GDP was positively correlated with the prevalence of nephrologists. We found that patients with ESKD in high income countries were older, spent more time on dialysis (reflecting increased dialysis availability), and were more likely to receive a kidney transplant than patients in LMICs.…”
Section: Discussionmentioning
confidence: 93%
“…A single hemodialysis session in Ethiopia has an out-of-pocket cost of $100, which is 11% of the per capita Ethiopian GDP and is, therefore, inaccessible to almost everyone. 17 analysis, per capita GDP was positively correlated with the prevalence of nephrologists. We found that patients with ESKD in high income countries were older, spent more time on dialysis (reflecting increased dialysis availability), and were more likely to receive a kidney transplant than patients in LMICs.…”
Section: Discussionmentioning
confidence: 93%
“…The findings of the study revealed the patients' perceptions of increased social support and decreased levels of anxiety, and their likelihood of engaging in higher levels of self-care. It is also noted in the study conducted by Gebrie (2023), that their ability to maintain their treatment and their mental fortitude depends critically on the financial, physical, and companion support they receive from friends, family, and other acquaintances.…”
Section: Perceived Social Support Of the Hemodialysis Patientsmentioning
confidence: 99%